Too Many Arabic Treatises on the Operation of the Astrolabe in the Medieval Islamic World: Athīr Al-Dīn Al-Abharī’s Treatise on Knowing the Astrolabe and His Editorial Method - Mimura, Taro (Medieval encounters, 2017)
In the medieval Islamic world, many scholars engaged in astronomy composed books on astrolabe, especially treatises on how to operate it (called “Treatises on the Operation of the Astrolabe”) such as Book of the Astrolabe (Kitāb al‐Asṭurlāb) by Kūshyār ibn Labbān (fl. second half of the tenth century ce); however, most of them had similar contents. One might ask why these scholars sought to write their own treatises of this kind, even though they differed little from existing works on the subject? To answer this question, I compare Kūshyār’s Book of the Astrolabe (Kitāb al‐Asṭurlāb) and Athīr al‐Dīn al‐Abharī’s (d. 1262 or 1265) Treatise on Knowing the Astrolabe (Risāla fī maʿrifat al-Asṭurlāb), which was written under the strong influence of Kūshyār’s Book: a comparison between them reveals that they presupposed the use of their own astrolabes. This analysis shows that many Arabic treatises on the operation of the astrolabe had their novelty at least guaranteed by the uniqueness of a specific astrolabe presupposed by each author.